STRATEGI GURU DALAM MENGEMBANGKAN DISIPLIN POSITIF PADA ANAK TK - Sumiati, Cucum; Patilima, Hamid (Journal of Early Childhood Education (JECE), 2023)
Teachers have a central role in shaping and developing positive discipline in kindergarten children. Positive discipline has been recognized as an effective approach in managing children’s behavior by emphasizing principles such as open communication, active teaching and positive reinforcement. This study aims to explore various strategies and tactics used by teachers in developing positive discipline in kindergarten children, especially in Assuryaniyah Islamic Kindergarten in Bekasi City. The research method used is qualitative research with a case study approach. The informants in this study were 2 classroom teachers. Data collection techniques used observation, interviews and documentation. From the analysis, the researchers found that in developing positive discipline in children, the teacher’s strategy was not only to act as a model (example) who showed appreciation, patience and empathy in interacting with children, but also as a motivator who supported the process of developing positive discipline in children, becoming a facilitator in designing clear rules and fair consequences so that children understand the consequences of their actions, becoming a mediator (intermediary) who helped children solve problems wisely and becoming an evaluator by collaborating with parents in developing positive discipline in children.